Calculus Flipped Classroom: Pre-class & In-class Learning Outcomes and Students’ Perception - Kinzie Feliciano Pinontoan; Mario Walean; Chervando Chrisye Pinontoan (International Journal on Emerging Mathematics Education, 2020)
Flipped classroom is a blended learning implements e-learning and does not eliminate face-to-face sessions in the classroom. This study applied flipped classroom to calculus lectures to determine students’ perceptions and learning outcomes. Learning outcomes were investigated in pre-class sessions, in-class sessions, and compared to the traditional class. All materials in the flipped classroom used screencast via Google Classroom. The sample was calculus class students at Prisma University. Data were collected using a questionnaire, written tests, and Kahoot online test. Data analysis was performed descriptively and statistically using the 2-sample t-test and paired t-test. The results showed no significant difference in the average score of learning outcomes between the pre-class of calculus flipped classroom and traditional class. However, the average score after in-class sessions was higher than the average score in the traditional class. Furthermore, positive responses were shown by students who lectured with the flipped classroom.